2022
DOI: 10.1016/j.ecss.2021.107736
|View full text |Cite
|
Sign up to set email alerts
|

Responses of a macrobenthic community to seasonal freshwater flow in a wet-dry tropical estuary

Abstract: Wet-dry tropical estuaries are extreme environments driven by wet season rainfall and runoff events. The biota associated with these systems are highly adapted to large fluctuations in salinity. There are few examples globally where water extraction for human needs has not yet had a major impact on freshwater flow volumes and seasonal variability in these systems. Therefore, this study examined the importance of seasonally variable flow on intertidal macrobenthic (>0.5 mm mesh size) abundance and species compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Our study also showed that areas with floating-leaved plants had a higher density of macrobenthos (Table 1). Correspondingly, shorebirds mainly feed on macrobenthos [17], and there is a clear positive correlation between their abundance and that of macrobenthos [3,18,19,44]. Shorebirds also showed a higher abundance in the floating-leaved plant area (Table 3), and their total density was significantly positively correlated with the total density of macrobenthos (Figure 6).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our study also showed that areas with floating-leaved plants had a higher density of macrobenthos (Table 1). Correspondingly, shorebirds mainly feed on macrobenthos [17], and there is a clear positive correlation between their abundance and that of macrobenthos [3,18,19,44]. Shorebirds also showed a higher abundance in the floating-leaved plant area (Table 3), and their total density was significantly positively correlated with the total density of macrobenthos (Figure 6).…”
Section: Discussionmentioning
confidence: 89%
“…Macrobenthos are the main prey of shorebirds [17], the abundance of which is significantly and positively correlated with the number of available macrobenthos [3,[18][19][20]. The distribution of shorebirds also largely depends on macrobenthos, and the capacity to partition available resources varies according to shorebird morphological and behavioral diversity [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that, in addition to impacting river flows, dams have important impacts on sediment dynamics and geomorphic processes [30,[72][73][74]. Rivers are estimated to transport about 90% of all dissolved and particulate matter that is deposited in the ocean, and the total annual sediment transported by rivers is estimated at about 19 billion tons, representing a very important driver of hydrological changes and the morphological evolution of estuaries and adjacent sea areas [75,76].…”
Section: Effects Of Dam Construction On Sediment Flux Into the Oceanmentioning
confidence: 99%
“…The reservoir dams in the Yangtze River Basin have had little effect on the runoff of the Yangtze River. From 2002 to 2016, before and after the construction of the Three Gorges Dam, the annual runoff at the Yichang, Shashi, and Datong monitoring stations located in the downstream reaches of the Yangtze River increased by 5.28-8.55% [74]. However, as a consequence of the water storage function of the Three Gorges Dam, the monthly runoff of the Yangtze River has changed greatly due to seasonal regulation [79,80].…”
Section: Effects Of Dam Construction On Sediment Flux Into the Oceanmentioning
confidence: 99%